Quality end of life care. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Johnstone, Ros; Fowell, Andrew
Abstract : Implemented on an all-Wales basis in 2000 the Welsh Integrated Care Pathway (ICP) for the last days of life has gone from strength to strength. Starting with 38 sites there are now over 100 sites using the ICP to deliver quality end of life care in a variety of settings including: hospitals hospices specialist in-patient units and in the community. Centrally collecting and analysing the ICP variance sheets has permitted quality monitoring and benchmarking exercises facilitating feedback and informing the on-going development of the ICP tool Variance monitoring shows that the incidence of goal variances associated with the management of pain, agitation and excess respiratory secretions or rattle have decreased over time, indicating a higher proportion of goal achievement and improvement in optimum care. The same tool is used for cancer and non-cancer patients with no differences between the two patient groups on length of time on the pathway or frequency of goal related reported variances. The ICP has recently undergone a thorough overhaul and the new pathway has been taken up and used throughout the principality. Conclusion: It is possible to implement, sustain and maintain the use of the ICP over a wide geographical area and for different patient groups, ensuring that quality end of life care can be delivered in different care settings. Currently there is a strong move to develop and implement an ICP for end of life care in intensive care units, adopting the same model of implementation therefore facilitating a Wales wide implementation monitoring and feedback process.